(3cJGH aVd GdLgGO hJYdje GdaQhSjIs - (3YjSi Hf ESeGYjd GdMfaj GdGbUQGFjs
(3ChdgG (B:s
(3GdMeO ddg fGUQ ef CWGYg hGJbGg abGd SHMGfg (B( (3hGYOhG dge eG SGJWYJe ef bhI hef QHGW GdNjd (B) (3aCeOge HGdNjhd GdShGHb hGdLjGO GddhGMb s
(3BNQgG (B:s
(3jfJgi CKfGA GdHGH GdNGeS ef GdJYdje GdKGfi ef cJGH eaQOGJ HfhO GdTjN fLe GdOjf GdGMOH QMeg Gddg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQJH GdGHLOi s
Keywords: (3GdaQGSIs